2015
DOI: 10.17507/tpls.0502.26
|View full text |Cite
|
Sign up to set email alerts
|

Vowel Classification and Vowel Space in Persian

Abstract: Abstract-This article aims to develop an acoustic vowel space in Persian speech. There are several aspects in this survey which make it different from what has been done before. The first is related to the issue of speech material. The need for more natural choice in voice qualities in recent years exhort us not relying on citation form or artificial sound produced in laboratories. Furthermore, the formant frequencies were not extracted from specified vowels, in specified context. In contrast, we are intereste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Several studies have focused on the acoustic features of vowels -first and second formants -in Farsi (Ansarin 2004;Aronow et al 2017;Esfandiari et al 2015;Ghaffarvand Mokari et al 2017;Mohammadi et al 2011). Ghaffarvand Mokari et al (2017) reported the F0, F1, F2, and F3 and the duration of the Farsi vowels of 28 male and 25 female Farsi monolinguals with Tehrani dialect.…”
Section: Acoustics Of Farsi Vowelsmentioning
confidence: 99%
“…Several studies have focused on the acoustic features of vowels -first and second formants -in Farsi (Ansarin 2004;Aronow et al 2017;Esfandiari et al 2015;Ghaffarvand Mokari et al 2017;Mohammadi et al 2011). Ghaffarvand Mokari et al (2017) reported the F0, F1, F2, and F3 and the duration of the Farsi vowels of 28 male and 25 female Farsi monolinguals with Tehrani dialect.…”
Section: Acoustics Of Farsi Vowelsmentioning
confidence: 99%
“…Studies that did incorporate acoustic measurements used formal readings of literary prose (Samareh 1977), self-recordings of formal speech (Toosarvandani 2004), or measurements from a database of recordings (FarsDat) uncontrolled for dialect, age, or socioeconomic status (Gharavian 2000). In two purely acoustic studies that measured only formant values and not duration, Esfandiari et al (2015) rely on news broadcast recordings, while Ansarin (2004) recorded only six words as pronounced by female speakers.…”
mentioning
confidence: 99%